Covid-19 Lockdown Challenges or New Era for Higher Education - Didenko, Iryna (2021)
The COVID-19 lockdown caused hard time for higher education: unexpected shift to online. This research was conducted among 50 first-year Bachelor’s Degree students and 50 first-year Master’s Degree students of the Faculty of Economics of Taras Shevchenko National University of Kyiv. The objective of the study was to identify the challenges that each focus group faced and students’ satisfaction rate in education under lockdown. Quantitative methods were used for collecting data and Excel tools for processing the results The findings demonstrated relatively average satisfaction rate among the 1st-year Bachelor level students due to a number of factors: lack of self-study skills, lack of background, lack of experience. However, 1st-year Master level students demonstrated relatively high satisfaction rate. The reason for this is that they are quite experienced and competent, therefore, they require less facilitation from the professors, their background knowledge is enough to allow them to search the necessary data in the Internet, their analytical and reasoning skills are developed enough to let them process obtained information, critically evaluate it and produce reasonable conclusions. The findings of this research allow to assume that after lockdown it might be worth reconsidering the format of learning for Master’s Degree Programs and shift from conventional face-to-face learning to blended or even distance learning.